Case studies in exercise and sport sciences: A powerful tool to bridge the science-practice gap - Halperin, I. (International Journal of Sports Physiology and Performance, 2018)
Despite the progress made by the scientific exercise community in collaborating and communicating with nonscientist coaches, there is room for improvement. Coaches find research difficult to understand, feel that their interests are not being addressed by exercise research, and rely on peer discussion to further their coaching knowledge base while consuming few peer-reviewed articles. One useful strategy to bridge the science-practice gap is with case studies. In addition to furthering our understanding of the physiology, psychology, and training schedules of elite athletes, case studies can serve (1) as a useful communication channel with coaches if presented as narratives and (2) to establish and strengthen relationships between scientists and coaches, leading to fruitful research collaborations. The purpose of this invited commentary is to discuss these 2 less-recognized benefits of case studies and propose a way to incorporate case studies more frequently alongside group-based studies.